Docking and small angle X-ray scattering studies of purine nucleoside phosphorylase - de Azevedo, W. F.; dos Santos, G. C.; dos Santos, D. M.; Olivieri, JR; Canduri, F.; Silva, R. G.; Basso, L. A.; Renard, G.; da Fonseca, I. O.; Mendes, M. A.; Palma, Mario Sergio [UNESP]; Santos, D. S. (Elsevier B.V., 2003)
Docking simulations have been used to assess protein complexes with some success. Small angle X-ray scattering (SAXS) is a well-established technique to investigate protein spatial configuration. This work describes the integration of geometric docking with SAXS to investigate the quaternary structure of recombinant human purine nucleoside phosphorylase (PNP). This enzyme catalyzes the reversible phosphorolysis of N-ribosidic bonds of purine nucleosides and deoxynucleosides. A genetic deficiency due to mutations in the gene encoding for PNP causes gradual decrease in T-cell immunity. Inappropriate activation of T-cells has been implicated in several clinically relevant human conditions such as transplant rejection, rheumatoid arthritis, lupus, and T-cell lymphomas. PNP is therefore a target for inhibitor development aiming at T-cell immune response modulation and has been submitted to extensive structure-based drug design. The present analysis confirms the trimeric structure observed in the crystal. The potential application of the present procedure to other systems is discussed. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: geometric docking; SAXS; purine nucleoside phosphorylase; bioinformatics